Scheduling divisible real-time loads on clusters with varying processor start times - Chuprat, Suriayati; Baruah, Sanjoy (2008)
Recent research in real-time divisible load theory (RT-DLT) has addressed the problem of distributing arbitrarily parallelizable real-time workloads among processors which become available at different instants in the future. Given a real-time job and the times as which the processors become available, we devise exact efficient algorithms to solve two important problems: (i) determine the smallest number of processors needed to complete this job by its deadline; and (ii) given a specific number of processors, determine the earliest completion time for the job on these processors.